P-59 Relationship between autonomic cardiac regulation at rest and indices of training load in recreational cyclists. (18th November 2016) - Weippert, M; Behrens, M; Mau-Moeller, A; Felser, S; Husmann, F; Zschorlich, V; Bruhn, S; Behrens, K
Abstract : Although cycling is one of the most popular aerobic exercises in competitive and non-competitive recreational sports, limited data exist regarding the acute physiological responses to a period of intensified training in recreational cyclists. Increases in training load typically occur, however in annual training camps. Thus, the aims of this observational field study were to (i) assess short-term autonomic, haematological and muscular responses to increased training load in recreational active male cyclists; and (ii) to elucidate, whether there is a correlation between autonomic response and indices of training load in this population. It was hypothesised, that an increase of aerobic training volume leads to significant elevations of serum creatine kinase (S-CK), increases in morning heart rate, and alterations of indices of heart rate variability (HRV). Methods: Heart rate (HR) and its variability (HRV), serum creatine kinase (S-CK) and hematocrit (Hct) were measured in the mornings before (PRE) and following three consecutive training days (POST 1-3). Daily cycling distance, altitude difference, maximum temperature of the day differed between the training sessions and were: 105 km, 1800 m, 26°C for training day 1; 122 km, 1700 m, 20°C for training day 2, and 80 km, 1900 m, 20°C for training day 3, respectively. Results: Morning HR significantly increased during the training period (PRE: 52.2±6.7 bpm, POST 1: 58.8±7.0 bpm POST 2: 58.5±8.1 bpm, POST 3: 57.9±7.2 bpm; F(3, 33) = 11.182, p < 0.001, partial η 2 = 0.554). While the parasympathetically modulated HRV high frequency power (HFP) decreased from PRE to POST 1-3, no significant effect was found for normalised low frequency power (LFP n.u.; PRE: 0.60±0.23, POST 1: 0.74±0.13, POST 2: 0.69±0.20, POST 3: 0.68±0.21; F(3, 33) = 2.287, p = 0.101, partial η 2 = 0.203), a measure reflecting sympathetic HR modulation. Hct showed a progressive decrease across measurement days (PRE: 49.9±4.0%, POST 1: 46.5±5.1%, POST 2: 45.5±3.8%, POST 3: 43.2±3.4%; F(3, 33) = 11.909, p < 0.001, partial η 2 = 0.520). Average S-CK increased after the training, with three subjects showing above reference values at POST 1 and 2 (PRE: 90.0±32.1 U/L, POST 2: 334.7±487.6 U/L, POST 3: 260.1±303.4 U/L, POST 3: 225.1±258.8 U/L; (F(3, 33) = 3.996, p = 0.017, partial η 2 = 0.285). S-CK leakage was significantly associated with HR (r=0.452, p=0.002) and HFP after night rest (r=-0.492, p<0.001). Conclusion: Three days of increased aerobic training volume can be associated with hemodilution, parasympathetic withdrawal and increases in muscular damage seromarkers in recreational cyclists. Despite cycling is thought to be an activity inducing no or only minor elevations in seromarkers of muscular damage (Noakes, 1987), an intensified training period increased S-CK in our sample of recreational cyclists. At POST 2 S-CK value tended to decrease, possibly due to a repeated bout effect (McHugh, 2003). Morning HR and its variability reflected larger alterations in training load in our study. Furthermore, S-CK, a marker of muscular damage and/or training load, was associated with alterations of HR-derived indices of autonomic control, a finding that has been previously reported by only a few investigators (Buchheit et al., 2011).